Malformação congênita infanto-juvenil associada à exposição aos agrotóxicos, em região de tríplice fronteira: estudo de caso-controle - Tanaka, Carlos Eduardo Yukio (2023)
Excessive use of pesticides can cause negative effects on human health, including death. The occurrence of Congenital Malformations (CM) has been related to maternal and paternal exposure to pesticides, in different exposure periods. The aim of this study was to verify the association between pesticide exposure and the frequency of orthopedic CM in the western and southwestern border regions of Paraná. It was a case-control study conducted at the Rehabilitation Clinic of the FAG University Center with children and adolescents up to 18 years of age who were receiving or had received treatment at the institution since 2004. The control group consisted of children and adolescents in care or who had attended the Rehabilitation Center for some service, but whose clinical diagnosis did not include orthopedic CM. They were age-matched and three controls were selected for each case. The interview used a questionnaire formulated by the researchers based on the Protocol for the Evaluation of Chronic Pesticide Intoxication, developed by the Health Secretariat of the State of Paraná, taking into account the outcome of the study, parental, demographic, maternal and child exposure variables. Fifty-six children participated, 14 of them with a diagnosis of orthopedic CM, with mean age of 7.1±2.1 years and predominantly urban residence. Regarding pesticide exposure, the greatest contact occurred in adulthood, before the birth of the children and in both groups, both fathers and mothers lived in rural areas at some point in their lives, but did not remain in rural areas during the gestational period. Forty-two-point nine percent of the participants in the case group had been in contact with pesticides and 35.6% of the mothers had complications during pregnancy, such as threatened preterm delivery (21.4%); the same complication predominated in the control group (14.3%). The number of children and the presence of siblings with disabilities were statistically significant for the occurrence of orthopedic CM. Factors such as smoking, alcohol consumption, drug use and medication did not present statistically significant associations. It can be concluded that, in the group analyzed, there was no significant relationship between exposure during pregnancy and orthopedic CM for most of the outcomes, only for the number of children and the presence of a sibling with a disability.